Feasibility and Performance Studies of a Semi Active Journal Bearing. (2016) - Yogaraju, Raghu; Ravikumar, L.; Saravanakumar, G.; Shravankumar, C.; Kumar, V. Arun
Abstract: In this paper, details related to preliminary efforts made towards developing a novel semi-active journal bearing have been presented. The study which is predominantly experimental in nature uses a test rig designed and fabricated for the purpose of simulating a multi-lobed journal bearing and also to study the possibility of utilising smart materials for conversion of a circular bearing profile to a multi lobed bearing profile during operation. Preliminary experimental studies have indicated that while shape memory alloy (SMA) can be used as a medium to apply necessary forces at identified locations to obtain the desired profile shapes for a multi-lobe bearing configuration facilitating the development of semi active journal bearings, ovality ratios of the bearing profile under investigation ranging from 1.5 to 2 have been realised by suitable application of direct forces in opposing directions. The performance enhancement defined in terms of stiffness and damping of the newly configured bearing equivalent to two lobed bearing over the conventional bearing has been studied. The test rig is versatile in nature, with a facility to investigate varieties of semi active journal bearings. The study indicates an increase in dynamic stiffness and damping with increase in the ovality ratio of the semi-active journal bearings.